Nutrition and Irrigation Management for Florida HLB-Affected Trees - Tripti Vashisth; Davie Kadyampakeni; Jamie D. Burrow (EDIS)
To improve production of huanglongbing (HLB) affected trees, nutrition, irrigation, and soil pH should be considered together, because each can influence the efficacy of the others in overcoming the effects of HLB on tree performance. This two-sided poster published by the UF/IFAS Horticultural Sciences Department through the UF/IFAS Citrus Research and Education Center was written by Tripti Vashisth, Davie Kadyampakeni, and Jamie D. Burrow. https://edis.ifas.ufl.edu/hs1367